2012
DOI: 10.1177/1363461511433945
|View full text |Cite
|
Sign up to set email alerts
|

The mental health and psychosocial effects of organized violence: A qualitative study in northern Haiti

Abstract: Historically, organized violence has been a chronic pervasive problem in Haiti. We set out to elicit Haitians' views on its effects to guide the development of interventions. In March 2006 we studied a population in the slum area of Cap-Haitien, Haiti's second largest city, and the nearby towns of Milot and Limbe. A convenience sample of adults was asked to free list all current problems affecting victims of organized violence. Two major categories emerged: psychological problems and financial problems. The ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…Kalkile twòp and synonyms reflechi twòp , maladi kalkilasyon and zaminem reflect what seems to be a worldwide concern for excessive negative cognition. Versions of “thinking too much” have been reported in distressed populations in Zimbabwe (Patel, Simunyu, & Gwanzura, 1995), Ghana (Avotri & Walters, 1999), Sudan (Rasmussen et al, 2010), Uganda (Bolton, Abbo, Okello, Ekblad, Waako, & Musisi, 2008; Betancourt, Rubin-Smith, Beardslee, Stulac et al, 2011), Cambodians in the U.S. (Hinton, Hinton, Eng, & Choung, in press), and among South Asians living in Britain (Fenton & Sadiq-Sangster, 1996) and the U.S. (Karasz, 2005) – and even previously among Haitians in Haiti (as moun yo panse anpil ; Bolton et al, 2012). In Haiti, “thinking too much” is strongly associated with sadness and, if allowed to persist, is thought to potentially lead to psychosis (Fullard, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalkile twòp and synonyms reflechi twòp , maladi kalkilasyon and zaminem reflect what seems to be a worldwide concern for excessive negative cognition. Versions of “thinking too much” have been reported in distressed populations in Zimbabwe (Patel, Simunyu, & Gwanzura, 1995), Ghana (Avotri & Walters, 1999), Sudan (Rasmussen et al, 2010), Uganda (Bolton, Abbo, Okello, Ekblad, Waako, & Musisi, 2008; Betancourt, Rubin-Smith, Beardslee, Stulac et al, 2011), Cambodians in the U.S. (Hinton, Hinton, Eng, & Choung, in press), and among South Asians living in Britain (Fenton & Sadiq-Sangster, 1996) and the U.S. (Karasz, 2005) – and even previously among Haitians in Haiti (as moun yo panse anpil ; Bolton et al, 2012). In Haiti, “thinking too much” is strongly associated with sadness and, if allowed to persist, is thought to potentially lead to psychosis (Fullard, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Variations on this method have included the use of card sorts (Fullard, Kohrt, Keys, Khoury et al, 2012; Rasmussen et al, 2011), focus groups (van Ommeren, Sharma, Thapa, Makaju et al, 1999), and qualitative interviewing with key informants (Miller, Omidian, Quraihsy, Quraihsy et al, 2006) to better define the mental health constructs of interest. In Haiti, ethnographic methods have resulted in identifying idioms of distress that reference the heart ( kè ) and head ( tèt ) disorders that roughly map onto emotional (mood and anxiety) and psychotic problems, respectively (Bolton, Surkan, Gray, & Desmousseaux, 2012; Fullard, Kohrt, Keys, Khoury et al, in press; Keys, Khort, Fullard, Khoury et al, 2012; Wagenaar, Hagaman, Kaiser, McLean, & Kohrt, 2012). …”
mentioning
confidence: 99%
“…Third, if providers are trained in individual EBT focused on one clinical problem (e.g., depression), a referral system would be needed to link individuals with counselors trained to treat this problem area. Fourth, many studies in LMIC have demonstrated that comorbidity is common with limited distinction among diagnostic categories used in the United States and Europe (Bolton, Surkan, Gray, & Desmousseaux, 2012; Murray et al, 2006; Rasmussen, Katoni, Keller, & Wilkinson, 2011). After these types of qualitative studies, when various EBTs are being considered, the single diagnostic focus of these treatments forces the choice to treat only a certain group among those that need help.…”
mentioning
confidence: 99%
“…4,15 However, there is converging evidence that symptoms of depression and reactions to traumatic stress show great concordance to widely used diagnostic criteria for depression and PTSD in community-based samples of Haitians. 14,22 Third, this clinic-based sample is not a representative sample of patients in the community. Many of the patients who sought out our psychiatric consultation or were referred for psychiatric consultation may have had more severe illness or may have been more knowledgeable about clinic-based initiatives.…”
Section: Discussionmentioning
confidence: 99%